Finding aid IFPRI repository 2015-2019 - International Food Policy Research Institute (International Food Policy Research Institute, 2015)
This is an export of ebrary.ifpri.org of publications for the years 2015 to 2019. All records are migrated to CGSpace individually and this table is retained for the purpose of archival reference.